Identifying the job competencies of Generation Z hotel employee in an intelligent environment in China (International Journal of Management and Sustainability, 2024)
This study aims to identify and enhance the job competencies of Generation Z hotel employees in China, focusing specifically on how intelligent environments influence their job roles. Employing a mixed-methods approach, the research integrates focus group interviews with five groups to explore how job roles evolve in response to intelligent environments and uses questionnaires with 167 participants to develop a competency framework. The investigation addresses various dimensions of the intelligent hotel environment, including work support, internal communications, customer experience, and staff-customer interactions. Results show that the sense of responsibility towards customer interactions escalates to another level after hotels adopt an intelligent environment. Furthermore, this study establishes a job competency framework with 3 dimensions and 33 evaluation factors for Generation Z hotel employees, validated through Exploratory Factor Analysis and Confirmatory Factor Analysis. The framework of job competencies assists hotels in refining job competency assessment standards, developing robust performance appraisal systems, planning effective career development pathways, and designing targeted training programs. We expect these enhancements to significantly enhance the operational excellence and competitive advantage of hotels in China.